The Eastern Caribbean Currency Union : Institutions, Performance, and Policy Issues - Randall, Ruby (Occasional Papers; Occasional Paper ;, 2000)
The Eastern Caribbean Central Bank is one of just a few regional central banks in the world and the only one where the member countries have pooled all their foreign reserves, the convertability of the common currency is fully self-supported, and the parity of the exchange rate has not changed. This occasional paper reviews recent developments, policy issues, and institutional arrangements in the member countries of the Eastern Caribbean Currency Union, and looks at the regional financial system, its supervision, and the central bank's initiatives to establish a single financial space. The paper includes a large amount of statistical information that is not readily available elsewhere from a single source.